The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3389/fpsyg.2013.00567
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation patterns resulting from learning letter forms through active self-production and passive observation in young children

Abstract: Although previous literature suggests that writing practice facilitates neural specialization for letters, it is unclear if this facilitation is driven by the perceptual feedback from the act of writing or the actual execution of the motor act. The present study addresses this issue by measuring the change in BOLD signal in response to hand-printed letters, unlearned cursive letters, and cursive letters that 7-year-old children learned actively, by writing, and passively, by observing an experimenter write. Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 60 publications
7
54
0
2
Order By: Relevance
“…We found that it was more involved in Chinese writing than in English writing, and that reading did not activate the Exner’s area in either language. Previous studies have also found that viewing letters/reading activated the left MFG but not the Exner’s area [29,41][42], even though the authors did not explicitly and clearly discuss the different functions of the left MFG and Exner’s area in reading and writing. Longcamp, 2003 found that reading and writing overlap at the left MFG (-53, 4, 40), but only writing showed activation in the more medial Exner’s area (-28, -1, 65), although it was not directly tested whether the Exner’s area is more activated in writing than reading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that it was more involved in Chinese writing than in English writing, and that reading did not activate the Exner’s area in either language. Previous studies have also found that viewing letters/reading activated the left MFG but not the Exner’s area [29,41][42], even though the authors did not explicitly and clearly discuss the different functions of the left MFG and Exner’s area in reading and writing. Longcamp, 2003 found that reading and writing overlap at the left MFG (-53, 4, 40), but only writing showed activation in the more medial Exner’s area (-28, -1, 65), although it was not directly tested whether the Exner’s area is more activated in writing than reading.…”
Section: Discussionmentioning
confidence: 99%
“…In reading, imaging studies have found that viewing letters/words/characters that were learned through writing evoked greater activation in this region than viewing those learned by passive viewing. This effect was located in the left IFG at (-56, 4, 19) [40], at (-42, 6, 20) [28], the ventral premotor cortex at (-51,-2,41) [41], the ventral precentral gyrus at (-49,-5,44) [42] and (-53,-6,41) [43]. These regions are all proximal to the left MFG reported to be differentially active in Chinese versus English.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been implicated in learning; the insula and claustrum are BOLD-activated during active, but not passive learning (Kersey and James, 2013). Given the prevalence of claustral abnormalities in memory disorders, the role of the claustrum in the creation of fluency heuristics may be due to its involvement in recall.…”
Section: Macro-connectomicsmentioning
confidence: 99%
“…Furthermore, there is mounting evidence that many children with reading disabilities, including dyslexia, also have writing impairments (Berninger, 2006). Neuroscientific research shows that brain mechanisms that support visual letter categorization only respond to letters in pre-literate children after handwriting (printing) practice, but not after visual-auditory (the usually taught method), typing, or tracing practice (James, 2010; James & Engelhardt, 2012; Kersey & James, 2013). Taken together, results suggest a crucial role for handwriting practice in the development of letter categorization ability and of brain networks supporting letter perception and reading.…”
mentioning
confidence: 99%